PENGARUH ARUS KAS BEBAS, STRUKTUR KEPEMILIKAN, DAN PERTUMBUHAN PERUSAHAAN TERHADAP MANAJEMEN LABA - ANGELINA LORENZIA; Riki Sanjaya (E-Jurnal Akuntansi TSM, 2022)
The purpose of this study is to provide empirical evidence about the effect of free cash flow, ownership structure, firm’s growth, return on assets, financial leverage, firm size, firm age, and audit quality on earnings management. The ownership structure on this study consists of managerial ownership and institutional ownership. Samples of this research were selected based on the purposive sampling method and resulted in 122 nonfinancial companies listed on Indonesia Stock Exchange (IDX) during the period of 2017-2019. The data obtained from these samples were analyzed using multiple regression analysis. Earnings management in this study computed using the modified Jones Model 1995. The results of this research show that free cash flow, firm’s growth, return on assets, financial leverage, and firm size has effect on earnings management, while ownership structure (managerial ownership and institutional ownership), firm age, and audit quality have no influence on earnings management.